2022
DOI: 10.1093/mrcr/rxac027
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment for eosinophilic granulomatosis with polyangiitis causing severe myocarditis followed by cardiac magnetic resonance

Abstract: A 38-year-old woman had a history of asthma for 20 years. Bullous lesions had appeared in her left side of the back. Two months before admission, and biopsy revealed eosinophilic cellulitis. She experienced numbness in both legs one month later. She was admitted to our hospital for emergency treatment due to chest pain and loss of consciousness. Emergency coronary angiography revealed triple-vessel vasospasm. She had cardiac arrest for four minutes during the examination. We suspected eosinophilic granulomatos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The administration of mepolizumab, as a monoclonal antibody against interleukin-5 (IL-5), has been shown to result in a significant reduction in peripheral blood and tissue eosinophils. Although our patient unfortunately could not gain access to this drug, its therapeutic effect has been mentioned in some previous case reports ( 12 - 14 ). For example, Sakurai et al ( 14 ) reported a 50-year-old woman diagnosed as EGPA with cardiac involvement.…”
Section: Discussionmentioning
confidence: 64%
“…The administration of mepolizumab, as a monoclonal antibody against interleukin-5 (IL-5), has been shown to result in a significant reduction in peripheral blood and tissue eosinophils. Although our patient unfortunately could not gain access to this drug, its therapeutic effect has been mentioned in some previous case reports ( 12 - 14 ). For example, Sakurai et al ( 14 ) reported a 50-year-old woman diagnosed as EGPA with cardiac involvement.…”
Section: Discussionmentioning
confidence: 64%